Problematika Pembelajaran di Era Pandemi COVID-19 Stud Kasus: Indonesia, Filipina, Nigeria, Ethiopia, Finlandia, dan Jerman - Sutanto Trijuni Putro; Mawanti Widyastuti; Hastuti Hastuti (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2020)
The Covid-19 pandemic has brought significant changes in the world of learning. Many countries are closing schools and universities to prevent the spread and break the chain of the covid-19 virus. As a result of the closure, distance learning was implemented through various existing media. Each country has different conditions, so learning during this pandemic experiences different challenges and problems. These differences are interesting to study to provide an overview of what is happening in the country and can be used as an evaluation in the future. This study was conducted through literature studies with various sources, both journals and selected online news. The selected countries are Indonesia, Philippines, Ethiopia, Nigeria, Finland and Germany. The selection is done randomly without any particular background, but representing the existing continents. Based on the results of the study, the responses, strategies and obstacles that occurred in the education sector during the pandemic was listed. The strategies, successes, and obstacles that occurred in each country were influenced by the readiness of infrastructure up to human resources, as well as the initial conditions of the country before the pandemic.